2015
DOI: 10.1515/joim-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Family Involvement in the Firm and Exports in the Family SME: Is the Manager’s International Orientation Influential?

Abstract: Does the family involvement affect exports in the family firm? The literature seems to support this view even if the direction and magnitude of this impact remains controversial. Drawing on the perspectives of agency [Chrisman et al. 2004;Schulze et al. 2001] and stewardship as applied to family firms [Davis, Schoorman and Donaldson 1997] and also on socio-emotional wealth perspective [Gómez-Mejía et al. 2007], this study seeks to contribute to this debate by studying the influence of family involvement on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
(54 reference statements)
0
7
0
2
Order By: Relevance
“…For instance, building foreign partner relationships could be difficult due to the cultural differences (Ojala, 2015). SME managers are usually reluctant to lose control of the firm's operations (Basly, 2015). Although maintaining control can lower a firm's export intensity (Cerrato & Piva, 2010), some SMEs prefer to keep more control over export operations (e.g., by seeking local vehicles to foster exports such as promotion agencies or subsidies).…”
Section: The Role Of Foreign Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, building foreign partner relationships could be difficult due to the cultural differences (Ojala, 2015). SME managers are usually reluctant to lose control of the firm's operations (Basly, 2015). Although maintaining control can lower a firm's export intensity (Cerrato & Piva, 2010), some SMEs prefer to keep more control over export operations (e.g., by seeking local vehicles to foster exports such as promotion agencies or subsidies).…”
Section: The Role Of Foreign Partnersmentioning
confidence: 99%
“…The scope of export operations and the levels of export intensity achieved by SMEs appear to be determined by the availability of resources to deal with international markets (e.g., Dhanaraj & Beamish, 2003) However, SMEs are typically resourceconstrained, an aspect that characterizes them and may reduce their capacity to export (Achtenhagen, 2011;Suárez-Ortega & Álamo-Vera, 2005). Besides, exporting is considered as a challenging (Calabrò, Mussolino, & Huse, 2009) and risky activity for this type of firms (Basly, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Exporting entails complexity (Basly, 2015) and risk (Krauss, 2017). It is a challenging task particularly for SMEs (Calabrò et al, 2009).…”
Section: Intentions To Pursue Export Expansionmentioning
confidence: 99%
“…Foreign sales usually present sharp peaks and slumps (Majocchi et al, 2005). Exporting is regarded as a risky activity (Basly, 2015;Kuivalainen et al, 2013) and apparently more challenging for SMEs due to internal resource constraints that may limit their capacity to expand abroad (Achtenhagen, 2011;Su arez-Ortega and Álamo-Vera, 2005).…”
Section: Intentions To Pursue Export Expansionmentioning
confidence: 99%
“…However, given the multiplicity of managerial functions, the owner-manager is expected to fulfill, in most instances, the management of HR in family-owned SMEs is done informally as this is amenable with the competence of the owner-manager who in most instances is not an HR expert (Dundon & Wilkinson, 2018). Basly (2015) admitted to this analysis and reported that in family-owned SMEs, the family may try to keep the HR function under the control of the owner-manager who in most instances will lack expertise in HR management. This state of affairs according to Herrero (2017) may lead to the perception that such formalisation leads to complex managerial practices that may compel the owner-manager to reconsider any formalisation overtures.…”
Section: Effort Expectancy Of Formalising Human Resources Practicesmentioning
confidence: 99%